Impacto do uso droga imunomoduladora no tratamento da artrite séptica por Staphylococcus aureus - Machado, Priscila Maria Colavite [UNESP] (2013)
Staphylococcus aureus is considered the more important etiological agent of septic arthritis. In this context, the main objective of this work was to investigate the arthritogenic capacity of standard S. aureus strains, producer of superantigens (SAgs). We also tested the therapeutic effectiveness of an association antibiotic and an immunomodulatory drug in this model. C57BL/6 male mice were initially infected by retro-orbital plexus with different strains. Development and severity of arthritis were followed during 14 days, through determination of body weight, clinical score and incidence of arthritis, histopathological changes, determination of colony forming units, evaluation of local infiltration of Th subsets by real time PCR and cytokine production by spleen cells. The results were organized in three manuscripts. In the first one we compared the arthritogenic ability of 5 S. aureus strains. We found that the strains ATCC 19095 SEC+, N315 ST5 TSST-1+ and S-70 TSST-1+ determined severe, intermediate and discrete arthritis, respectively. In the second study we characterized the arthritis caused by the ATCC 19095 SEC+ strain. This type of arthritis was characterized by high clinical scores associated with synovial proliferation, intense inflammation, pannus formation, cartilage destruction and bone erosion. In the final manuscript we evaluated the therapeutic potential of the combination bewteen cloxacilin (bactericidal antibiotic) with tacrolimus (immunomodulator). The administration of these two drugs was less effective in controlling the disease than the antibiotic alone